The divine comedy : the inferno, the purgatorio, and the paradiso - Dante Alighieri, 1265-1321.; Ciardi, John, 1916-1986. (New York : New American Library, 2003)
Belonging in the immortal company of the great works of literature, Dante Alighieri's poetic masterpiece, The Divine Comedy, is a moving human drama, an unforgettable visionary journey through the infinite torment of Hell, up the arduous slopes of Purgatory, and on to the glorious realm of Paradise -- the sphere of universal harmony and eternal salvation.
Now, for the first time, John Ciardi's brilliant and authoritative translations of Dante's three soaring canticles -- The Inferno, The Purgatorio, and The Paradiso -- have been gathered together in a single volume. Crystallizing the power and beauty inherent in the great poet's immortal conception of the aspiring soul, The Divine Comedy is a dazzling work of sublime truth and mystical intensity.
The Inferno -- The Purgatorio -- The Paradiso.
Includes bibliographical references.
Also issued online.
Keywords: Dante Alighieri, -- 1265-1321 -- Translations into English; Dante Alighieri, -- 1265-1321.; Dante Alighieri, -- 1265-1321.; Dante Alighieri, -- 1265-1321.; Dante Alighieri, -- 1265-1321.